Robust Control Charts for Monitoring Process Mean of Phase-I Multivariate Individual Observations. (9th June 2013) - Variyath, Asokan Mulayath; Vattathoor, Jayasankar
Abstract : Hoteling'sT 2 control charts are widely used in industries to monitor multivariate processes. The classical estimators, sample mean, and the sample covariance used inT 2 control charts are highly sensitive to the outliers in the data. In Phase-I monitoring, control limits are arrived at using historical data after identifying and removing the multivariate outliers. We propose Hoteling'sT 2 control charts with high-breakdown robust estimators based on the reweighted minimum covariance determinant (RMCD) and the reweighted minimum volume ellipsoid (RMVE) to monitor multivariate observations in Phase-I data. We assessed the performance of these robust control charts based on a large number of Monte Carlo simulations by considering different data scenarios and found that the proposed control charts have better performance compared to existing methods.